Hubungan Adaptasi Akademik dan Regulasi Diri terhadap Burnout Akademik Mahasiswa PAI Generasi Z - Hidayatus Salehah; Nor Alini; Patimah Patimah; Surawan Surawan (LP2M Universitas Islam Ahmad Dahlan, 2026)
The development of higher education in the digital era requires Generation Z students to be able to adapt to various increasingly complex academic demands. This study aims to determine the relationship between academic adaptation and self-regulation with academic burnout among Generation Z students of Islamic Religious Education. This study uses a quantitative approach with a correlational descriptive method. The research sample consisted of 20 Islamic Religious Education students from the 2023 cohort at the State Islamic University of Palangka Raya, selected through purposive sampling. Data were collected using Likert scale questionnaires and analyzed through validity tests, reliability tests, descriptive statistics, and Pearson correlation. The results of the study indicate that academic adaptation is in the high category, self-regulation is in the fairly high category, and academic burnout is in the low category. The correlation test results showed a significant negative relationship between academic adaptation and academic burnout, whereas self-regulation had a negative but not significant relationship. These findings imply that strengthening academic adaptation needs to be a primary concern in efforts to prevent academic burnout among Generation Z PAI students.